2008
DOI: 10.1007/s10571-008-9286-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Survival of Melanopsin-expressing Retinal Ganglion Cells After Injury is Associated with the PI3 K/Akt Pathway

Abstract: In the present study, we studied the factors that contribute to the injury-resistant property of melanopsin-expressing retinal ganglion cells (mRGCs). Since phosphatidylinositol-3 kinase (PI3 K)/Akt signaling pathway is one of the well-known pathways for neuronal cell survival, we investigated the survival of mRGCs by applying the PI3 K/Akt specific inhibitors after injury. Two injury models, unilateral optic nerve transection and ocular hypertension, were adopted using Sprague-Dawley rats. Inhibitors of PI3 K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 34 publications
(49 reference statements)
3
34
1
Order By: Relevance
“…Moreover, the P13K/Akt signaling pathway can contribute to the neurite outgrowth of differentiated RGCs [40]. Therefore, this pathway is needed to inhibit the occurrence of apoptosis and promote axonal regeneration in both glaucoma and optic neuropathy [41, 42]. …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the P13K/Akt signaling pathway can contribute to the neurite outgrowth of differentiated RGCs [40]. Therefore, this pathway is needed to inhibit the occurrence of apoptosis and promote axonal regeneration in both glaucoma and optic neuropathy [41, 42]. …”
Section: Discussionmentioning
confidence: 99%
“…However, the nature of AION-induced injury to ipRGCs is not known. As indicated by histopathologic studies in animals and humans in other optic neuropathies, ipRGCs may have greater resistance to injury and death compared to other vision-mediating retinal ganglion cells131416171819. In this study, we assessed the intrinsic melanopsin photoresponse of ipRGCs as a measure of their functional integrity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is a growing body of evidence that ipRGCs display greater resistance to certain models of ganglion cell injury and death13141516171819. This robustness of ipRGCs is the basis for the visual-pupillary dissociation that is observed in patients with isolated hereditary mitochondrial optic neuropathy.…”
mentioning
confidence: 99%
“…Several different animal models of glaucoma have been investigated to determine if melanopsin RGCs are injury-resistant. Melanopsin-expressing RGCs were found to be selectively spared compared to conventional RGCs in a rat model of chronic ocular hypertension induced by laser photocoagulation of the episcleral and limbal veins P h y s i o l B i o c h e m P h a R m a c o l 1 6 2 ( 2 0 1 2 ) of the eye with resultant elevated intraocular pressure (IOP) (Li et al 2006(Li et al , 2008. In a different rat model of episcleral vein cauterization, melanopsin-expression RGCs were not apparently spared (Drouyer et al 2008;Wang et al 2008) and functional deficits in irradiance responses were reported (Drouyer et al 2008).…”
Section: Iprgcs and Retinal Diseasementioning
confidence: 99%